P2.026 Audit of Adherence to UK National Guideline For Management of Epididymo-Orchitis. (13th July 2013) - Whitfield, C; Rodgers, S
Abstract : Background: The UK guideline for epididymo-orchitis management makes recommendations about appropriate diagnostic tests, treatment regimes and health promotion principles. This audit compares our clinic's performance with reference to these guidelines. Methods: Case notes of patients diagnosed with epididymo-orchitis over seven months were reviewed. Details of sexual orientation, investigations, treatment and management were recorded. Results: There were 84 patients comprising 61(71.2%) heterosexual men, 22(26.2%) men who had sex with men (MSM), and 1(1.2%) bisexual man. Fifty one (60.7%) men had all four recommended microbiological investigations of gramme stained urethral smear, urethral swab for N. gonorrhoeae culture, first pass urine (FPU) for nucleic acid amplification tests for N. gonorrhoeae and C. trachomatis, and microscopy and culture of mid-stream urine (MSSU) for bacteria . Of the 84 patients, 81(96.4%) had 3 tests taken of urethral smear, swabs and FPU, but MSSU was only performed in 57(67.9%) men. Ten (11.9%) men were diagnosed with chlamydia and 3(3.6%) with gonorrhoea, and 82(97.6%) patients received appropriate antibiotic treatment according to the guidelines. Advice on rest, analgesia and scrotal support was poorly documented (9.5%; 9.5%; 8.3% respectively). Guidance about abstinence from sex and partner notification (PN) was documented in 65(77.4%) cases and explanation about the condition recorded in 54(64.3%) cases. A leaflet was offered in 3(3.6%) cases. Seventy six (90.5%) patients had a follow up appointment offered at 2 weeks but only 42(55.3%) patients attended. At the review, PN was completed for all patients. A written action plan was recorded in 100% of men with ongoing symptoms. Conclusions: Recommended antibiotic treatment was nearly always offered to patients. However general advice and written documentation were poor and non-attendance at follow up was high. Urine culture testing and documentation should be significantly improved for initial management, and a robust system developed to assess compliance with treatment, PN and symptom resolution.